Measuring the M&A value of control and synergy in Central and Eastern European transition economies with the case of Avast -AVG acquisition - David Moreira; Karel Janda (European Financial and Accounting Journal, 2017)
We examine the valuation of synergies and control in mergers and acquisitions (M&A) in Central and Eastern European (CEE) transition economies. We determine this value based on comprehensive contemporaneous financial findings extracted from the Thomson Reuters database. Worldwide the market of mergers and acquisitions (M&A) is increasing, reaching in 2016 a value of 6.000 billion EUR globally. Among the CEE transition economies, the M&A total value in the same period was 50 billion EUR. It is widely accepted that between 60% and 80% of M&As are unsuccessful in value creation, so we further research evidences about an alternative framework to value the M&A also qualitatively. We develop a valuation model for prediction of the value of control and synergy in M&A deals. We suggest further directions for analysis in the field of M&A value creation, and recommend an alternative to the most used earning per share metric to enhance the predictability and transparency of valuation worldwide.
Keywords: G34; 650; Acquisitions; Control; Corporate Governance; Mergers; Synergy